2004
DOI: 10.1111/j.1365-294x.2004.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential population structuring of two closely related fish species, the mackerel (Scomber scombrus) and the chub mackerel (Scomber japonicus), in the Mediterranean Sea

Abstract: Population genetic structures of the mackerel (Scomber scombrus) and chub mackerel (Scomber japonicus) were studied in the Mediterranean Sea. Fragments of 272 bp (S. scomber) and 387 bp (S. japonicus) of the 5′‐end of the mitochondrial control region were sequenced from spawning individuals collected off the coasts of Greece, Italy, Spain, and Portugal. High levels of mitochondrial control region haplotypic diversity (> 0.98) were found for both Scomber species. Nucleotide diversity was higher in the mackerel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
115
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 71 publications
(112 reference statements)
15
115
1
5
Order By: Relevance
“…Coalescence time of T. delaisi populations based on mitochondrial control region data is shown in the column 4. Parameters were estimated using FLUCTUATE (Kuhner et al 1998 Costagliola et al 2004), the chub mackerel (Scomber japonicus, Zardoya et al 2004), the withe sea-bream (Diplodus sargus, Bargelloni et al 2005) and the Norway lobster (Nephrops norvegicus, Stamatis et al 2004) were described as having high gene Xow levels between the Atlantic and the Mediterranean and no signs of an Atlantic-Mediterranean divide. These contrasting patterns may stem from diVerent biological characteristics of the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coalescence time of T. delaisi populations based on mitochondrial control region data is shown in the column 4. Parameters were estimated using FLUCTUATE (Kuhner et al 1998 Costagliola et al 2004), the chub mackerel (Scomber japonicus, Zardoya et al 2004), the withe sea-bream (Diplodus sargus, Bargelloni et al 2005) and the Norway lobster (Nephrops norvegicus, Stamatis et al 2004) were described as having high gene Xow levels between the Atlantic and the Mediterranean and no signs of an Atlantic-Mediterranean divide. These contrasting patterns may stem from diVerent biological characteristics of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on diVerent marine organisms have shown contrasting results. Some species exhibit little gene Xow and strong genetic divergence between Atlantic and Mediterranean populations (Kotoulas et al 1995;Borsa et al 1997;Chikhi et al 1997;Naciri et al 1999;Aurelle et al 2003;Bargelloni et al 2003Bargelloni et al , 2005, while others show very high levels of gene Xow (Bargelloni et al 2003(Bargelloni et al , 2005Costagliola et al 2004;Duran et al 2004;Zardoya et al 2004). An emerging pattern is shown in cases of closely related species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have focused on the relationship between the eastern Atlantic and Mediterranean (Alvarado Bremer et al, 2005;Bargelloni et al, 2003Bargelloni et al, , 2005Costagliola et al, 2004;Domingues et al, 2005;Lemaire et al, 2005;Naciri et al, 1999;Stamatis et al, 2004;Zardoya et al, 2004). In contrast, little is known about genetic relationships between populations of the Macaronesian islands (Azores, Madeira, Canaries, and Cape Verde; Almada et al, 2005;Guillemaud et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Within European Atlantic waters, spawning grounds and migrations are not well known. The lack of genetic differentiation across the northeast Atlantic and the Mediterranean Sea does not support the existence of homing behaviour to spawning grounds (Zardoya et al 2004).…”
Section: Introductionmentioning
confidence: 99%